Redevelopment of abandoned Highland Towers as memorial landscape - Zubaidi, Anis Hazirah; Hj. Baharuddin, Zainul Mukrim; Mansor, Mazlina (IIUM Press, 2020)
The aim of this project is to reclaim the abandoned area of Highland Towers and redevelop the area into a memorial park. The objectives of the project are to rejuvenate the historical value of the place, to revitalize the abandoned area, and to propose green spaces. The process included identifying issues and the solutions for the proposed design of the project.. Data collection method consisted of primary and secondary data. The proposed design considers the slope condition and the historic value of the site. Ergo, any development proposed are considering the stability of the slope condition.